Climbing the longevity pyramid: overview of evidence-driven healthcare prevention strategies for human longevity - Martinović, Anđela; Mantovani, Matilde; Trpchevska, Natalia; Novak, Eva; Milev, Nikolay B.; Bode, Leonie; Ewald, Collin Y.; Bischof, Evelyne; Reichmuth, Tobias; Lapides, Rebecca; Navarini, Alexander; Saravi, Babak; et al. (Frontiers in Aging, 2024)
Longevity medicine is an emerging and iterative healthcare discipline focusing on early detection, preventive measures, and personalized approaches that aim to extend healthy lifespan and promote healthy aging. This comprehensive review introduces the innovative concept of the “Longevity Pyramid.” This conceptual framework delineates progressive intervention levels, providing a structured approach to understanding the diverse strategies available in longevity medicine. At the base of the Longevity Pyramid lies the level of prevention, emphasizing early detection strategies and advanced diagnostics or timely identification of potential health issues. Moving upwards, the next step involves lifestyle modifications, health-promoting behaviors, and proactive measures to delay the onset of age-related conditions. The Longevity Pyramid further explores the vast range of personalized interventions, highlighting the importance of tailoring medical approaches based on genetic predispositions, lifestyle factors, and unique health profiles, thereby optimizing interventions for maximal efficacy. These interventions aim to extend lifespan and reduce the impact and severity of age-related conditions, ensuring that additional years are characterized by vitality and wellbeing. By outlining these progressive levels of intervention, this review offers valuable insights into the evolving field of longevity medicine. This structured framework guides researchers and practitioners toward a nuanced strategic approach to advancing the science and practice of healthy aging.